The level of social communication difficulties in Autism Spectrum children from the viewpoint of their teachers - Abo Fakhr, Ghassan; elmardeny, Ghalia (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed to identify the level of social communication difficulties in Autism Spectrum children from the viewpoint of their teachers ,and to know whether there is any differences in the level of difficulties related to gender variable, and. to achieve this goal the researcher used the translated study of children Autism Spectrum by Bilal Audeh, and The scale of social communication, prepared by the researcher. the study included: 12 children from the age of 5-10 years diagnosed with autism spectrum (6 males- 6 females) ,and one of the most important results: The existence of statistically significant differences between the level of gestural expressions difficulties and the friendship difficulties with peers; this difference was in favor of friendship difficulties with peers. : the existence of statistically significant differences between the level of non-verbal expressions difficulties and difficulties of sharing the interests with others; this difference was in favor of sharing interests with others. the existence of statistically significant differences between the level of friendship difficulties with peers and the difficulties of sharing interests with others; this difference was in favor of the difficulties of sharing interests with others. the existence of statistically significant differences between the level of the social communication difficulties by sex of the child variable according to the non-verbal expressions difficulties and friendship difficulties with peers, but there are no statistically significant differences between the level of difficulties in participation with others as concerns the sex of the child variable